Photosynthetic photon flux density affects fruit biomass radiation-use efficiency of dwarf tomatoes under LED light at the reproductive growth stage - Ke, Xinglin; Yoshida, Hideo; Hikosaka, Shoko; Goto, Eiji (Frontiers in Plant Science, 2023)
This study aimed to analyze the effects of photosynthetic photon flux density (PPFD) on fruit biomass radiation-use efficiency (FBRUE) of the dwarf tomato cultivar ‘Micro-Tom’ and to determine the suitable PPFD for enhancing the FBRUE under LED light at the reproductive growth stage. We performed four PPFD treatments under white LED light: 200, 300, 500, and 700 μmol m–2 s–1. The results demonstrated that a higher PPFD led to higher fresh and dry weights of the plants and lowered specific leaf areas. FBRUE and radiation-use efficiency (RUE) were the highest under 300 μmol m–2 s–1. FBRUE decreased by 37.7% because RUE decreased by 25% and the fraction of dry mass portioned to fruits decreased by 16.9% when PPFD increased from 300 to 700 μmol m–2 s–1. Higher PPFD (500 and 700 μmol m–2 s–1) led to lower RUE owing to lower light absorptance, photosynthetic quantum yield, and photosynthetic capacity of the leaves. High source strength and low fruit sink strength at the late reproductive growth stage led to a low fraction of dry mass portioned to fruits. In conclusion, 300 µmol m−2 s−1 PPFD is recommended for ‘Micro-Tom’ cultivation to improve the FBRUE at the reproductive growth stage.